2005
DOI: 10.1111/j.1743-6109.2005.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Vardenafil, a Selective Phosphodiesterase 5 Inhibitor, in Patients with Erectile Dysfunction and Arterial Hypertension Treated with Multiple Antihypertensives

Abstract: Introduction Vardenafil, a phosphodiesterase type 5 (PDE5) inhibitor, was evaluated in a prospective trial in the primary care setting involving hypertensive men with ED who were receiving at least one antihypertensive medication. Aims To investigate the safety and efficacy of flexible-dose vardenafil therapy compared with placebo in PDE5 inhibitor-naïve subjects with arterial hypertension and ED. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
67
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 40 publications
16
67
0
2
Order By: Relevance
“…14,24 In studies assessing the use of vardenafil in patients on antihypertensive medicines, there was no increase in adverse events. 22 Thus, PDE5 inhibitors can be safely administered with usual antihypertensive agents including diuretics, beta blockers, calcium blockers and angiotensin receptor blockers. There is a precaution, however, with alpha blockers that will be explained below.…”
Section: Does the Addition Of Pde5 Inhibitors To Antihypertensive Agementioning
confidence: 99%
See 1 more Smart Citation
“…14,24 In studies assessing the use of vardenafil in patients on antihypertensive medicines, there was no increase in adverse events. 22 Thus, PDE5 inhibitors can be safely administered with usual antihypertensive agents including diuretics, beta blockers, calcium blockers and angiotensin receptor blockers. There is a precaution, however, with alpha blockers that will be explained below.…”
Section: Does the Addition Of Pde5 Inhibitors To Antihypertensive Agementioning
confidence: 99%
“…21 Vardenafil has also been shown to be effective for treating ED in hypertensive men on antihypertensive agents. 22 Van Ahlen et al 22 studied the safety and efficacy of vardenafil in men with arterial hypertension and ED, receiving at least one antihypertensive medicine. This was a multicenter, randomized, double-blind placebo-controlled study of 354 patients.…”
Section: The Association Of Hypertension With Edmentioning
confidence: 99%
“…A value of 19.47 for Cochran's Q 3 was reported with an associated value of 33.23% (assuming 13 degrees of freedom) for Higgins' I. 2,4 Although the test failed to reject the null hypothesis of homogeneity, it has been noted that this test lacks adequate power. 5 As a result, investigators often use a ¼ 0.10 as a threshold for statistical significance when performing the Q-test.…”
mentioning
confidence: 99%
“…For example, a recent study in PDE5-inhibitor-naïve men with ED and hypertension showed average EF domain score improvements with vardenafil of 10.7 points from baseline. 2 The authors acknowledge that 'in cases of insufficient data, standard deviations (SD) were substituted. The estimation was based either on figures presenting confidence intervals (CIs), standard errors, or SDs or on other studies with the same agent, which reported SD for treatment and placebo group.'…”
mentioning
confidence: 99%
“…39 In subjects with ED and hypertension, vardenafil did not alter the blood pressure of subjects taking antihypertensives. 40 In healthy subjects, tadalafil caused very small changes in blood pressure that were not considered to be clinically relevant. 38 Tadalafil reduced mean standing blood pressure by À4.6 mm Hg in patients with hypertension, but this unlikely to be of major concern.…”
Section: Vardenafil and Tadalafil Have Advantages Over Sildenafil S Dmentioning
confidence: 99%